Further Twenty Years of Pathologies? Is Rational Choice better than it used to be?. Issue 3 (21st August 2014) - Hug, Simon
Abstract Twenty years ago the publication of "Pathologies of rational choice" by Donald Green and Ian Shapiro (1994) stimulated a large debate about the usefulness of rational choice approaches in political science. While the publication of this book has fruitfully led rational choice scholars to be more attentive to links between theoretical models and their empirical implications, some misunderstandings about the theoretical contributions of this approach still affect the discipline. Based on a brief summary about the debate I show the directions in which the rational choice literature has evolved and discuss some recent significant contributions.